Osteometric Evaluation of Human Skull for Sex Determination: A Comparative Study - Karan Jain1, Ninad Nagrale2, Ranjit Ambad3, Nandkishor Bankar4, Swapnil Patond5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Sex determination from analysis of bony remains is one of the most important arduous jobfor medicolegal experts, especially in cases where identity of the deceased person is in question. Aims& objectives: Our study focuses on evaluation of different osteometric parameters of skull which willbe helpful for sex determination.Material and Method: Current study was conducted on 60 human skullbones & they were studied by using calipers for various osteometric measurements. Results: In our studywe observed that, skull length, interorbital breadth, biorbital breadth, maxillo-alveolar breadth, maxilloalveolarlength, bizygomatic breadth & nasion-prosthion length are the statistically significant variables &are good determinants for sex than rest of the parameters. As compared to them, cranial breadth & orbitalheight are poor parameters for sex determination. Conclusion: Human Skull bone as a whole & it’s differentmeasurements taken from anatomical landmarks & their osteometric analysis is a good determinant for sexof an individual.